Impact of specific inactive dry yeast application on grape skin mechanical properties, phenolic compounds extractability, and wine composition. (February 2019) - Giacosa, Simone; Ossola, Carolina; Botto, Riccardo; Río Segade, Susana; Paissoni, Maria Alessandra; Pollon, Matteo; Gerbi, Vincenzo; Rolle, Luca
Abstract: Foliar treatments using two products based on Saccharomyces cerevisiae inactive dry yeast derivatives with specific formulations for white and red varieties were tested in two consecutive vintages on Vitis vinifera L. cv. Chardonnay, Cortese, and Nebbiolo grown in Piedmont (north-west Italy). The possible elicitor effect of the foliar treatment was assessed at harvest on the chemical composition and mechanical properties of grape berries. The accumulation and extractability of phenolic compounds in Nebbiolo grape skins were also studied. Wines were produced and analysed in terms of technological parameters, color characteristics, free volatile composition, and phenolic compounds. The treatments induced an +16 μm average increase in berry skin thickness, which makes the grapes more resistant to physical damages and pathogenous attacks. In Nebbiolo, this treatment enhanced the accumulation of anthocyanins (+33 mg/kg on average). However, the obtained results pointed out a vintage effect. In 2015, few significant differences between wines made from control and treated grapes were found. Instead, in 2016, Nebbiolo treated wines had a slightly worse chromatic quality as a consequence of lower contents of phenolic compounds, but they were richer in relative amounts of malvidin-3-glucoside. Graphical abstract: Unlabelled Image Highlights: Foliar treatments based on inactive dry yeasts were tested on grape varieties. A tendency to increased berry skin thickness values in treated grapes was found. Berry skin anthocyanin accumulation was affected by the treatment in some cases. A vintage effect was observed on wine color characteristics and phenolic composition. Nebbiolo wines from treated grapes were richer in free volatile esters.